Analisis Kebutuhan Ruang Parkir Science Technopark Universitas Tribhuawana Tunggadewi Malang - Mau , Maria Febiola Soi; Arifianto , Andy Kristafi; Primasworo , Rifky Aldila (Fakultas Teknik Universitas Tribhuwana Tunggadewi, 2023)
The student development center named Science Technopark is located at Tribhuwana Tunggadewi (UNITRI) and serves as a hub for the development of scientific education faculties. The problem that arises is the need for parking spaces due to the increasing student population and car ownership. This research aims to assess the parking space requirements of UNITRI Science Technopark located at Jalan Telagawarna, Tlogomas, Malang City by considering the existing conditions. This type of research explores specific demographics or samples using positivist quantitative research methodology to evaluate preconceived premises. Four-wheeled vehicles only require eight parking spaces, while two-wheeled cars require a total of 97 SRPs. The 60o parking pattern has a higher SRP (98 SRP) than the alternative when taking into account the two-wheeler parking pattern. The SRP and four-wheel SRP of 8 is the most effective parking pattern that will be utilized at Science Technopark Unitri Malang after many parking models have been analyzed. The maneuverability of vehicles when entering and exiting the parking lot is improved with this angle of parking arrangement.